Candy Bee: innovating pollen into modern snacks for beekeepers in Kampung Madu Tourism Village - Agung Witjoro; Claresia Tsany Kusmayadi; Halimatus Sa'diyah; Cassandra Permata Nusa; Ilmi Dewi Astuti; Dinar Arsy Anggraini (University of Merdeka Malang, 2025)
Kampung Madu Tourism Village in Bringin Village, Kediri, is renowned as a center for natural honey production. However, the lack of product diversification has limited the economic value for the local community. This community engagement program utilized bee pollen, a nutrient-rich byproduct of beekeeping, as the main ingredient for the innovative candy product,